Collaborative Governance dalam Pembangunan Masyarakat Perbatasan di Kabupaten Merauke - Andri Irawan; Aenal Fuad Adam (Department of State Administration - Musamus University, 2023)
The development of border areas aims to realize the border paradigm as the homeland of the Republic of Indonesia and needs to be carried out comprehensively, in the sense not only through a welfare approach but also through a security and environmental approach. For this reason, collaborative governance is one of the concepts that can be applied in developing border areas. This research was conducted using a descriptive method and a qualitative approach in Sota District, which is an area directly adjacent to Papua New Guinea. The results of the study indicate that collaborative governance in the development of the RI-PNG border area in the Sota District has not gone well. Indicators of starting conditions and intermediate outcomes have been seen from several programs such as the formation of community groups for Pokos honey entrepreneurs, eucalyptus oil processors, and ant nest tea processors. However, when viewed from the indicators of the collaborative process and institutional design, there has not been an ideal collaboration between the government, the private sector, and universities. Where it can be seen that all community empowerment activities are still dominated by the government, in this case, the Regional Border Management Agency, the Natural Resources Conservation Center, the Wasur National Park Center, and Merauke Regency. Ideally, in a collaborative process, universities and the community should be involved as implementers and balancers of the programs provided by the government in improving the welfare of the community.